Modeling of Monocrystalline PV Cell Considering Ambient Conditions in Baghdad City - Abd Al-Wahed, Mohammed E.; Abdullateef, Osamah F. (Al-Khwarizmi Engineering Journal, 2017)
Abstract The environmental conditions are important factors, because they affect both the efficiency of a photovoltaic module and the energy load. This research was carried out experimentally and modeling was done in MATLAB –Simulink by monitoring the variation in power output of the system with environmental conditions such as solar radiation, ambient temperature, wind speed, and humidity of Baghdad city. From the results, the ambient temperatures are inversely proportional to humidity and the output power performance of the system, while the wind speed is directly proportional with the output power performance of the system.   Keywords: Ambient temperature, cell temperature, humidity, Photovoltaic, solar radiation, wind speed.